The Gifted Rating Scales-Preschool/Kindergarten Form: An Analysis of the Standardization Sample Based on Age, Gender, and Race - Pfeiffer, Steven L (Roeper Rev, 2010)
This study reports on an analysis of the standardization sample of a rating scale designed to assist in identification of gifted students. The Gifted Rating Scales-Preschool/Kindergarten Form (GRS-P) is based on a multidimensional model of giftedness designed for preschool and kindergarten students. Results provide support for: the internal structure of the scale; no age differences across the 3-year age span 4:0–6:11; gender differences on only one of the five scales; artistic talent; and small but statistically significant race/ethnicity differences with Asian Americans rated, on average, 1.5 scale-score points higher than whites and Native Americans and 7 points higher than African American and Hispanic students. The present findings provide support for the GRS-P as a valid screening test for giftedness.